Geo-graphical Representation for Future Challenges in e.Education - Lo Tauro, Agata (GEOmedia, 2016)
This research is an opportunity to discuss how well investments in the development of surveying and mapping, through programmes such as GMES, may translate into operational, useful and relevant tools for environment professionals in the territory. Environmental analysis will be given the floor to provide the feedback on the experience with geomatic applications, and their needs under a pluri-disciplinary approach. The suitability of existing applications will be analyzed, as well as the efficiency of current support mechanisms for regions wishing to take up innovative applications and open data for sustainable management, heritage conservation and e.Education.The interdisciplinary research will analyze the following topics: territorial planning, environmental impact assessment, cultural heritage conservation, etc. from regional, national, European and International Strategies. This is a work in progress.